STRATEGI CSR DALAM INDUSTRI TAHU TEMPE KOTA KUPANG: ANTARA KEBERLANJUTAN DAN KESEJAHTERAAN MASYARAKAT - Ardi Sulistyo Pramono ,; Rizki Febriani , (Jurnal Cakrawala Ilmiah, 2025)
This research highlights an important focus on the implementation of Corporate Social Responsibility (CSR) in the tofu and tempe industry in Kupang City. The aim of this study is to understand how this industry applies CSR strategies while considering two crucial aspects: environmental sustainability and community welfare. Using a qualitative approach, this study explores how business actors manage their production impacts on the environment while striving to provide social benefits to workers and surrounding communities. This was conducted through interviews and direct observations at tofu and tempeh factory locations. The methods used included preparing a series of questions and conducting on-site visits to observe the conditions. The results indicate that most tofu and tempeh businesses in Kupang City are still in the early stages of implementing CSR strategies. Additionally, this study identifies several challenges faced, such as budget limitations, lack of stringent regulations, and low awareness of the importance of worker welfare in this industry